Burns and the Scottish folk-song - Kuosaitė, Elena (Literatūra, 1969)
Poems written in imitation of the motifs and melodies of Scottish folk-songs take an eminent place in Burns’s literary heritage. The poet’s interest in and acquaintance with the Scottish songs was determined by different biographical and historical factors. Burns recorded and transformed the Scottish folk-songs in different ways and forms: sometimes the poet made only slight alterations in the text of the songs, sometimes he changed the structure of the song by adding new stanzas to it or by reducing it, sometimes he took only some elements of the previous song (the title, the chorus, one or several lines etc.) and created a new song, sometimes he made quite original songs based on folklore and traditional images etc. There is an evident connection between the lyric and the music in Burns’s songs. The poet would never write the lyric until he had made himself completely familiar with the melody. Burns was well acquainted with the life of simple people and with their spiritual world. It helped him to penetrate into the very essence of folk-song and to catch its main features: simplicity, unaffected beauty, spontaneity and humaneness. He differs from many folk-song collectors of his time, who didn’t consider folk poetry as such but tried to revise it in the spirit of literary laws. Burns absorbed the very idiom of the folk-songs and transmitted them as if he himself were an anonymous popular bard. Burns has managed to infuse into his songs different folk elements. He knew how to recreate lyric, humorous and heroic aspects of the folk-songs, their poetic imagery and genuine folk feeling. At the same time they bear the stamp of his own personality. They reflect his social and moral principles, his poetic vision of life.